Food processing operations and scale-up - Valentas, Kenneth J. (Marcel Deker, 1991)
Introduction - Overview of the food industry - Financial analysis of capital projects - Food chemistruy - Soy complex - Ready-to-teat breakfast cereals - Dairy products - Orange juice case study - Food product development - Scale-upp of food processes - Dimensional anaysis.